Pelatihan Penguatan Kesehatan Mental di Sekolah Menuju Pendidikan Berkualitas - Riska, Muhammad; Ashari, Hilda; Makmur, Elfira; Sari, Dessy Ana Laila; Burhan, Muh. Iswal (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
Community Service focuses on the importance of empowering teachers in Mental Health Education within schools, particularly in Timika, a remote area in Eastern Indonesia. The frequent and unstable power outages cause difficulties in accessing the internet, and the region’s remote location makes it challenging for school teachers in Timika to obtain information about mental health. The goal of this Community Service initiative is to provide Mental Health Training in Schools Towards Quality Education, which will be implemented to enhance teachers' competencies in handling mental health issues. The ultimate objective is for teachers to become mentally healthy and skilled. As a result of this initiative, a learning environment that supports the emotional and psychological well-being of both teachers and students is created. The method used in this program includes training on children's mental health in the digital era, developing school vision and mission to support mental well-being, conducting social research and innovation, and providing parenting education. Mental health training strengthens the prevention of negative behaviors, thereby influencing the development of quality learning. The results of this program indicate that the training successfully formed a group of teachers who are concerned about mental health. Teachers became more proactive in raising awareness of the importance of mental health in schools. Additionally, this training initiative successfully facilitated educational outreach programs for parents and the surrounding community, both individually and in groups.